Membrane tension regulates water transport in yeast - Soveral, Graca (2015)
Evidence that membrane surface tension regulates water fluxes in intact cells of a Saccharomyces cerevisiae strain overexpressing aquaporin AQY1 was obtained by assessing the osmotic water transport parameters in cells equilibrated in different osmolarities. The osmotic water permeability coefficients (P-f) obtained for yeast cells overexpressing AQY1 incubated in low osmolarity buffers were similar to those obtained for a double mutant aqy1aqy2 and approximately three times lower (with higher activation energy, E-a) than values obtained for cells incubated in higher osmolarities (with lower E-a). Moreover, the initial inner volumes attained a maximum value for cells equilibrated in lower osmolarities (below 0.75 M) suggesting a pre-swollen state with the membrane under tension, independent of aquaporin expression. In this situation, the impairment of water channel activity suggested by lower P-f and higher E-a could probably be the first available volume regulatory toot that, in cooperation with other osmosensitive solute transporters, aims to maintain cell volume. The results presented point to the regulation of yeast water channels by membrane tension, as previously described in other cell systems. (C) 2008 Elsevier B.V. All rights reserved.. - Fundacao para a Ciencia e Tecnologia [POCT1/AGR/57403/2004]. - This work was supported by Fundacao para a Ciencia e Tecnologia, POCT1/AGR/57403/2004. We thank Doctor Paulo Costa Lemos, REQUIMTE, Portugal, for the supervision on the epifluorescence experiments.